Voicing (Medical) Complexity in the Theatre of Sarah Kane: 4.48 Psychosis (1999) and its Stage Adaptation by Deafinitely Theatre (2018) (Altre Modernità, 2024)
This paper proposes a reading of Sarah Kane’s 4.48 Psychosis (1999) from a theoretical perspective combining medical humanities, disability, and performance studies (Henderson and Ostrander; Murray); the aim is to expand upon previous scholarship which sought to analyse Kane’s multifarious ways of aestheticising—and questioning—illness and pain (e.g. Guarracino, “Scene”; Simon; Soncini), by reading medical discourse through the notion of ‘complexity’ (Kuppers, Theatre; Siebers). Firstly, I will focus on how complexity comes to the surface through the dramatic text: as Jolene Armstrong has pointed out, the linguistic renderings of a psychotic mind—staged as a medical spectacle—make 4.48 Psychosis a peculiar case study because it is “less like a play than a prose poem intended for interpretative performance” (Armstrong 177). Secondly, I will look at how Deafinitely Theatre attempted to translate the dramatic text into a bilingual performance (i.e. in spoken English and British Sign Language), set in a mixed-reality environment (e.g. the incorporation of video material into the live performance). Ultimately, this dual dimension will hopefully shed new light on the degree of performability of (medical) complexity in 4.48 Psychosis.